2010
DOI: 10.4330/wjc.v2.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography: A new approach to myocardial function

Abstract: Echocardiography is the most common diagnostic method for assessing cardiac function but some limitations affect this technique. Until now, visual assessment of wall motion and thickening has allowed only a subjective evaluation of myocardial function and requires long-term training. Recently, new echocardiographic techniques have been introduced to evaluate myocardial mechanics. Tissue Doppler imaging (TDI) technique is limited by angle-dependency such that only deformation along the ultrasound beam can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
0
44
0
3
Order By: Relevance
“…Studies have demonstrated that STE‐based S and Sr from the short axis and long axis of LV myocardial deformation can assess VM in patients with ischemic heart disease . In our study, STE‐based S and Sr at LDDSE had a higher accuracy than semi‐quantitative wall‐motion analysis combined with LDDSE for the assessment of VM.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have demonstrated that STE‐based S and Sr from the short axis and long axis of LV myocardial deformation can assess VM in patients with ischemic heart disease . In our study, STE‐based S and Sr at LDDSE had a higher accuracy than semi‐quantitative wall‐motion analysis combined with LDDSE for the assessment of VM.…”
Section: Discussionmentioning
confidence: 55%
“…STE has mitigated the shortcomings of tissue Doppler assessment because it is based on two-dimensional imaging, thus the results are more accurate and reproducible. 14…”
Section: Introductionmentioning
confidence: 99%
“…Even in the different spatial directions, it provides an insightful look at cardiac remodeling. 12 Global area strain (GAS) that can be acquired using 3D-STE can define the deformation of the endocardial surface during contraction and relaxation of the LV myocardium. Also, LV twist (LVtw) represents a phenomenon that links systolic contraction with diastolic relaxation and plays a major role in cardiac physiology.…”
Section: Introductionmentioning
confidence: 99%